PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM PERJANJIAN KEMITRAAN PETERNAKAN - Priyono, Ery Agus (Diponegoro Private Law Review, 2018)
This study aims to determine the model of legal protection for parties in the livestock business against the contract clause in the form of partnership cooperation between nucleus and plasma. Legal protection for both employers and workers engaged in livestock business. The research method is normative law research using comparative approach, statutory approach, conceptual approach, and historical approach. The results of research indicate that in the legal protection for the parties can be done by means of the plasma, forming an association in order to be together as one of the parties who will make agreements with the core parties in case of partnership cooperation. This is done so that there is a balance in terms of negotiations in the preparation of contract clauses. So as to achieve a sense of justice, balance and protection of the basic rights of the parties who do the partnership. Keywords: Legal Protection, Livestock Industry, Contracts, Partnership